An ionic liquid process for mercury removal from natural gas1. Issue 18 (14th May 2015) - Abai, Mahpuzah; Atkins, Martin P.; Hassan, Amiruddin; Holbrey, John D.; Kuah, Yongcheun; Nockemann, Peter; Oliferenko, Alexander A.; Plechkova, Natalia V.; Rafeen, Syamzari; Rahman, Adam A.; Ramli, Rafin; Shariff, Shahidah M.; et al.
<x xml:space="preserve">Abstract</x> Efficient ionic liquid based mercury scrubbing technology from gram to ton scale.